Help Protect Florida’s Natural Areas from Invasive Plants: Circular12/AG108, 8/2018 - Enloe, S.F.; Langeland, K.A. (EDIS, 2018)
This document addresses the pressing issue of invasive plants in Florida's natural areas, threatening native habitats and biodiversity. With over half of Florida's land developed for agriculture or urban use, preserving remaining natural areas is crucial for ecological balance. Invasive plants like Brazilian pepper tree and Australian pine displace native species, disrupt natural processes, and pose economic and environmental risks. Regulations exist to control these plants, but public awareness and action are essential. The article emphasizes the importance of recognizing and removing invasive plants from private properties to prevent their spread. It advocates for using native plants in landscaping and seeks collaboration among property owners, land managers, and officials to protect Florida's ecosystems. Sharing information and raising awareness are key to effective conservation efforts.